2021
DOI: 10.3390/ijerph18136791
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in Disability Incidence among Japanese Adults Aged 75 Years and Older: A 4-Year Prospective Cohort Study

Abstract: The present prospective study investigated the regional differences and trajectories of new-onset disabilities among older adults in the districts within a city in Japan. We analyzed data from 5050 Japanese residents aged ≥75 years old (men/women: 2512/2538) who completed the Kihon Checklist (a self-reported questionnaire on frailty) and a questionnaire on medical history and social capital in Ikoma city in 2015. The incidence of disability was determined using the new certification of long-term care insurance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Many studies have reported that social participation has a strong relationship with health outcomes such as functional disability 3,4 and mortality 5 . We reported that there were regional differences in disability incidence among districts within a city and social participation preventive effects on disability 6 . Our findings highlight the importance of targeting smaller districts in this study.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Many studies have reported that social participation has a strong relationship with health outcomes such as functional disability 3,4 and mortality 5 . We reported that there were regional differences in disability incidence among districts within a city and social participation preventive effects on disability 6 . Our findings highlight the importance of targeting smaller districts in this study.…”
Section: Introductionsupporting
confidence: 55%
“…5 We reported that there were regional differences in disability incidence among districts within a city and social participation preventive effects on disability. 6 Our findings highlight the importance of targeting smaller districts in this study.…”
Section: Introductionmentioning
confidence: 61%
“…In this study, handgrip strength, usual walking speed, and skeletal muscle mass, which are essential for assessing sarcopenia, showed that a decrease in usual walking speed over time reflected worsening certification levels, with a cutoff value of 0.14 m/s decrease. Previous studies have searched for factors in the occurrence of new LTCI certification by older adults who are not eligible for LTCI or in the deterioration of LTCI levels by institutionalized residents ( Shimada et al, 2023 ; Ashida, Kondo & Kondo, 2016 ; Shimizu, Ide & Kondo, 2023 ; Matsumoto & Takatori, 2021 ; Jin et al, 2018 ). Our study is unique in that it focuses on older adults living “at home” while receiving LTCI services–that is, those whose functional ability is between that of healthy individuals who are not eligible for LTCI and those who live in institutions, and uses changes in LTCI certification levels as the main outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the factors contributing to LTCI have mainly followed older adults with no applicable LTCI for several years, searching for factors that contribute to the development of new LTCI needs ( Shimada et al, 2023 ; Ashida, Kondo & Kondo, 2016 ; Shimizu, Ide & Kondo, 2023 ; Matsumoto & Takatori, 2021 ). Previous studies analyzing changes in certification levels among LTCI recipients have several limitations regarding the assessment items and target individuals, including analyses focusing solely on basic characteristics ( Kumai & Ikeda, 2021 ; Ohnuma et al, 2016 ), analyses based on several basic characteristics and one functional assessment ( Kamiya et al, 2017 ), analyses combined participants with no applicable LTCI and those who already had LTCI certification ( Kawamura et al, 2021 ), and analyses of institutionalized residents ( Jin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%